Managing Productive Performance Appraisal: Sebuah Upaya Menjawab Kebutuhan Penilaian Kinerja Karyawan yang Bebas KKN - Sri Dwi Ari Ambarwati (Jurnal Siasat Bisnis, 2002)
Reviewing employee`s performance is always “a nettlesome project” and it’s becoming even more so. Performance review typically draw a less than favorable response from employees, and for managers the process is often considered time consuming and feel uncomfortable grading their staff. However, performance review must did by all organization because it will be useful to rise organization performance.  This paper will explain some tip how to create an appraisal process that is beneficial and productive, such as develop a performance management process, design spesific and relevan appraisal, promote 360-degree model and how do staff member use their time to achieve organization’s objectives.  This paper divided into six section including describe general concept of performance appraisal, what’s the standard and criteria in appraisal process to guide reviewer and employees, how employed a productive performance appraisal in organization, new way in performance appraisal is use of time and all discussion will be concluded in the last section.Key word: productives appraisal, 360-degree feedback, use of time